EFFECTS OF POTASSIUM ON MUNG BEAN YIELD COMPONENTS, YIELD, AND YIELD QUALITY UNDER DROUGHT STRESS - Zavira Nurul Rachmaniar; Eka Kartina; Aep Wawan Irwan; Fiky Yulianto Wicaksono (Gunung Djati Conference Series, 2026)
Mung bean (Vigna radiata L.) is an important crop contributing to global food security. However, its productivity is severely affected by drought stress, particularly during the growth and grain filling stages. Drought stress reduces yield components such as pod number, seeds per pod, and grain weight due to disruptions in physiological and metabolic processes. It also negatively impacts crop quality by limiting nutrient accumulation and grain development. Potassium plays an important role in increasing plant tolerance to drought stress through various mechanisms. At the physiological level, potassium increases the efficiency of photosynthesis, regulates stomatal function, and maintains cellular osmotic balance, allowing plants to maintain turgor and metabolic activity under conditions of water deficit. At the biochemical level, potassium activates antioxidant enzymes that mitigate oxidative damage caused by reactive oxygen species. Furthermore, potassium supports the translocation of assimilates from source to recipient organs, thus promoting pod formation and grain filling. Adequate potassium supply also improves crop quality, including better nutrient content and grain uniformity. The interaction between potassium and water availability exhibits a synergistic effect, with optimal potassium levels increasing water use efficiency and mitigating the negative impacts of drought stress. Therefore, proper potassium management combined with efficient irrigation strategies is crucial for maintaining mung bean productivity and quality under drought conditions, thus supporting a more adaptive and sustainable agricultural system.